A sorafenib-sparing effect in the treatment of thyroid carcinoma cells attained by co-treatment with a novel isoflavone derivative and 1, 25 dihydroxyvitamin D3. Issue 182 (September 2018) - Izkhakov, Elena; Sharon, Orli; Knoll, Esther; Aizic, Asaf; Fliss, Dan M.; Kohen, Fortune; Stern, Naftali; Somjen, Dalia
Highlights: ERα, ERβ, VDRmRNA and 1OHase are highly expressed in human papillary thyroid cancer (PTC). cDtboc and 1.25D inhibit cell proliferation in human PTC. cDtboc and 1.25D markedly amplify the inhibitory effect of sorafenib on cell proliferation in human PTC. Abstract: Background: Sorafenib improves progression-free survival in patients with progressive radioactive iodine-refractory differentiated thyroid carcinoma, but causes severe side effects. Estrogens may accelerate thyroid carcinoma cell growth. Our group recently reported that isoflavone derivative 7-(O)-carboxymethyl daidzein conjugated to N -t-boc-hexylenediamine (cD-tboc), a novel anti-estrogenic compound, retards the growth of both thyroid carcinoma cell lines and cultured human carcinoma cells. Vitamin D receptor (VDR) is expressed in malignant cells and responds to 1, 25 dihydroxyvitamin D3 (1.25D) by decreased proliferative activity in vitro . The purpose of this study was to examine the effects of vitamin D metabolites (VDM) on the expression of estrogen receptors (ERs), VDR, and 1OHase mRNA, and to evaluate the inhibitory effect of low doses of sorafenib in combination with cDtboc and VDM on cell proliferation in cultured human papillary thyroid carcinoma (PTC). Methods: In 19 cultured PTC specimens and 19 normal thyroid specimens, harvested during thyroidectomies from the same patients, expression levels of ERα, ERβ, VDR, and 1 alpha-hydroxylase (1OHase) mRNA (by quantitative real-time PCR) were determined at baseline and after treatment with VMD. Cell proliferation was determined by measurement of 3 [H] thymidine incorporation after treatment with sorafenib alone, sorafenib with added 1.25D or cD-tboc, and sorafenib with both 1.25D and cD-tboc added. Results: 1, 25D increased mRNA expression of all tested genes in the malignant and normal thyroid cells, while the ERα mRNA of the normal cells was unaffected. 1.25D dose-dependently inhibited cell proliferation in the malignant cells. The inhibitory effect of sorafenib on cell proliferation in the malignant cells was amplified after the addition of cDtboc and 1.25D, such that the maximal inhibition was not only greater, but also had been attained at a 10-fold lower concentration of sorafenib (20 μg/ml). This inhibition was similar to that of the generally used concentration of sorafenib (200 μg/ml) alone. Conclusions: The demonstration that low concentrations of cDtboc and 1.25D markedly amplify the inhibitory effect of sorafenib on the growth of human PTC supports the use of a 10-fold lower concentration of sorafenib. The findings may promote a new combination treatment for progressive radioactive iodine-refractory PTC.